1984
DOI: 10.1159/000149537
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Mode of Action of Ribavirin against Tobacco Mosaic Virus

Abstract: Ribavirin inhibited a specific step of tobacco mosaic virus (TMV) replication. Time-courses of sensitivity of TMV multiplication in asynchronous and synchronous infections demonstrated that ribavirin inhibited an early function that occurs prior to the period of viral RNA and protein synthesis. In the synchronous infection, ribavirin inhibited the synthesis of both single-stranded genomic RNA and double-stranded replicative form RNA when treatment began during the first 4 h, but there was no inhibition when tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 9 publications
0
12
1
1
Order By: Relevance
“…Precursor incorpora tion experiments confirmed that viral RNA and protein syntheses were inhibited. This is in contrast to other inhibitors examined, 2-thiouracil [17] and ribavirin [18], which pre vent early steps of TMV multiplication.…”
Section: Discussioncontrasting
confidence: 82%
“…Precursor incorpora tion experiments confirmed that viral RNA and protein syntheses were inhibited. This is in contrast to other inhibitors examined, 2-thiouracil [17] and ribavirin [18], which pre vent early steps of TMV multiplication.…”
Section: Discussioncontrasting
confidence: 82%
“…Taiwan and chileno by employing sequential thermotherapy at 32°C for a week, 36°C for Direct and immediate suppressive effects of exposure to 40°C on the synthesis of host and viral RNAs and on the activity of viral replicase were demonstrated in cowpea and tobacco plants infected by various viruses. However, when the plants were transferred after a few hours at 40°C to an optimal temperature, host RNA synthesis was resumed immediately, while virus synthesis was delayed (Dawson and Lozoya Saldana 1984). The effect on viral RNA synthesis could probably be magnified if cycles of high and low temperature are repeated, thereby allowing elimination of the virus from growing parts of the plants in relative short periods of time (Stein et al 1991).…”
Section: Thermotherapy Applied To Intact Plantmentioning
confidence: 99%
“…2-Thiouracil inhibits a step that occurs later than the actinomycin D-sensitive step, but earlier than viral protein or RNA synthesis (Dawson and Schlegel, 1976a;Dawson and Grantham, 1983). Ribovirin and low concentrations of guanidine inhibit with the same kinetics and might inhibit the same process (Dawson, 1975;Dawson and Lozoya-Saldana, 1984). Cycloheximide and arabinofuranosyladenine inhibit a later step that coincides with protein and RNA syntheses (Dawson and Schiegel, 1976a;Dawson and Lozoya-Saldana, 1986).…”
Section: Replicationmentioning
confidence: 99%